2005
DOI: 10.1111/j.1440-1746.2005.03813.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B virus infection in the Asia–Pacific region and Africa: Review of disease progression

Abstract: Countries in the the Asia-Pacific region and Africa tend to have the highest prevalence of hepatitis B infection worldwide. Hepatitis B infection progresses from an asymptomatic persistently infected status to chronic hepatitis B, cirrhosis, decompensated liver disease and/or hepatocellular carcinoma. The aim of this review was to summarize rates and risk factors for progression between disease states in the Asia-Pacific region and Africa. A literature search was conducted employing MEDLINE and EMBASE (1975-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 45 publications
2
60
0
Order By: Relevance
“…This is the first long-term follow-up of a population-based cohort of chronic HBV carriers in SSA 3 31 32. We confirmed that the age-standardised rate of HCC in the chronic carriers in this study (67.3/100 000) was much higher than in the general population in The Gambia (22.1/100 000),27 which highlights the importance of controlling chronic HBV infection to prevent HCC.…”
Section: Discussionsupporting
confidence: 81%
“…This is the first long-term follow-up of a population-based cohort of chronic HBV carriers in SSA 3 31 32. We confirmed that the age-standardised rate of HCC in the chronic carriers in this study (67.3/100 000) was much higher than in the general population in The Gambia (22.1/100 000),27 which highlights the importance of controlling chronic HBV infection to prevent HCC.…”
Section: Discussionsupporting
confidence: 81%
“…3) [33]. The rate of progression from chronic hepatitis to cirrhosis is 1-4% in China and Taiwan [34].…”
Section: Progression Of Liver Disease and Mortality Rates In Hepatitis Bmentioning
confidence: 98%
“…In Korea, the 5, 10, 15, and 20-year progression rates from chronic hepatitis to cirrhosis are 9, 23, 36, and 48% respectively [35]. Thereafter, progression of compensated to decompensated cirrhosis occurs at an annual rate of 3.2-4.6% [33]. In a Taiwanese study, the mean age at decompensation in cirrhotic patients was 57.2 years [36].…”
Section: Progression Of Liver Disease and Mortality Rates In Hepatitis Bmentioning
confidence: 99%
See 1 more Smart Citation
“… HBV – hepatitis B virus; ALT – alanine aminotransferase 1 Percentage of all chronically infected individuals who are aware of their infection 2 This value was estimated from 96 , and then calibrated to yield approximately 25% mortality from untreated liver disease 86, 97 . 3 Personal communication with physicians in China 4 Some therapies are discontinued if the therapy suppresses the virus. This parameter is the fraction of patients who continue on drug therapy after the therapy has suppressed the virus into a “durable response.”…”
Section: Calculation Of Optimal Vaccination Levelmentioning
confidence: 99%